Climate Change Impacts and Adaptation in Water Resources and Water Use Sectors Case studies from Southeast Asia - Shrestha, Sangam (Springer Water,, 2014)
Climate change on earth is having significant impacts on water resources management in Southeast Asia. Knowledge of climate variations and climate change can be valuable for water resources management in agriculture, urban and industrial water supplies, hydroelectric power generation, and ecosystem maintenance. This book presents the findings of case studies on forecasting climate change and its impacts on water availability, irrigation water requirements, floods and droughts, reservoir inflows and hydropower generation, and crop yield in specific basins of Southeast Asian countries such as Thailand, Myanmar, and Vietnam. All case studies start by forecasting the climate change and investigating its impacts by employing several hydrological reservoir simulations and crop water requirement models. The findings provide sound and scientific advice for water managers on the real impacts of climate change and how to adapt to its many challenges.